The effectiveness of ERCP in managing preoperative complications of choledochal cysts in children and its role in facilitating early surgical intervention - Zhang, Tian; Wu, Wenjie; Shu, Yijun; Weng, Hao; Weng, Mingzhe; Zhou, Ying; Wang, Xuefeng (Frontiers in Pediatrics, 2025)
IntroductionCurrently, there is no established guideline for the application of ERCP in children with choledochal cyst. This study aimed to investigate the safety and effectiveness of ERCP in managing preoperative complications of choledochal cyst in children, as well as the timing for definitive surgery following ERCP.MethodsWe conducted a retrospective review of medical records for 68 pediatric patients who presented with complications of choledochal cyst, including pancreatitis and biliary obstruction combined with cholangitis. All patients underwent ERCP treatment followed by definitive surgery. The primary outcomes assessed included treatment efficacy, post-ERCP complication, and the impact of ERCP on definitive surgical procedures.ResultsAmong the 68 patients studied, 41 presented with pancreatitis, while the remaining patients had biliary obstruction and cholangitis. Sixty-five patients successfully completed their treatments, with 64 experiencing alleviation of symptoms. Significant improvements were observed in serum amylase levels and liver function tests following ERCP. Post-ERCP complications occurred in three cases, including one case of pancreatitis and two cases of infection. The median interval between ERCP and surgery was 11 days. There was no significant difference in primary outcomes, such as surgical duration, rate of minimally invasive surgery, conversion to open surgery, intraoperative bleeding volume, intraoperative blood transfusion, postoperative complications, or average length of hospital stay, between the early surgery group (≤2 weeks) and the late surgery group (>2 weeks).ConclusionsERCP was proved to be a safe and effective intervention for alleviating preoperative complications in pediatric patients with choledochal cyst. Early definitive surgery following ERCP did not significantly impact the perioperative outcomes of pediatric patients.